Digital Embedding System with Heater and Cooler - Nur Hudha Wijaya; Budiman Anggi Lesmana; Nishith Shahu; Irfan Ahmad; Rachmad Andri Atmoko (Journal of Robotics and Control (JRC), 2021)
Embedding is an anatomical pathology laboratory device that is very important for producing quality slices and is also a device used to process paraffin tissue, so that the tissue can be cut with higher precision using a microtom (slicer). From the process of melting paraffin crystals using a manual heating process with bunsen flame heaters (fire heaters) so that the paraffin crystals can be transformed from the crystal into liquid. While paraffin crystals that have been processed from the crystal to liquid form are poured into the mold and left to freeze. In this case, an embedding system device will be made equipped with heating and cooling. The temperature used for the liquefaction process is 50C while the temperature for cooling is 17C. After making the process of making device, experiment device, and retrieving data, the error percentage results were 0.016% at the heating temperature and 0.08% at the coolant temperature, and the percentage of heating samples obtained in the sample was 61.3%, while the percentage samples for parts coolers get a value of 92%